3-Methoxy-catalposide inhibits inflammatory effects in lipopolysaccharide-stimulated RAW264.7 macrophages. (March 2017) - Ryu, Hyung Won; Lee, Su Ui; Lee, Seoghyun; Song, Hyuk-Hwan; Son, Tae Hyun; Kim, Yeah-Un; Yuk, Heung Joo; Ro, Hyunju; Lee, Chong-Kil; Hong, Sung-Tae; Oh, Sei-Ryang
Highlights: 3-Methoxy-catalposide inhibits LPS-increased expression of COX-2 and iNOS. 3-Methoxy-catalposide inhibits LPS-increased expression of TNF-α, IL1β and IL-6. 3-Methoxy-catalposide inhibits both LPS-activated MAP kinases and NF-κB translocation into cell nucleus. Abstract: Pseudolysimachion rotundum var. subintegrum is utilized as a traditional herbal remedy to treat cough, bronchitis, and asthma in Korea, Russia, China, and Europe. Here, we show that 3-methoxy-catalposide, a novel iridoide glycoside isolated from P. rotundum var. subintegrum has the anti-inflammatory activity in lipopolysaccharide (LPS)-stimulated macrophages. The chemical structure of 3-methoxy-catalposide was determined by NMR, optical rotation and HRESIMS. In in vitro experiment, RAW264.7 cells were treated with 3-methoxy-catalposide for 2 h before exposure to LPS for different times. Inflammatory gene and protein expressions were assayed using RT-PCR and ELISA. Activities of signal proteins were examined using western analysis. Our results demonstrated that 3-methoxy-catalposide significantly inhibits the expression of cyclooxygenase (COX)-2 and inducible nitric oxide synthase (iNOS) in RAW264.7 cells stimulated by LPS, thereby suppressing the release of prostaglandin E2 (PGE2 ) and nitric oxide (NO). Moreover, 3-methoxy-catalposide markedly reduced the LPS-induced expression of pro-inflammatory genes, such as interleukin (IL)-6, IL-1β, and TNF-α. Further, 3-methoxy-catalposide inhibited both LPS-induced activation of three MAP kinases (ERK 1/2, JNK, and p38) and the nuclear translocation of NF-κB and AP-1. These results support that 3-methoxy-catalposide may be a promising candidate for inflammation treatment.